The effect of welding current on the mechanical properties of aluminium to copper material using Tungsten Innert Gas welding technology - Azwinur, Azwinur; Saifuddin, Saifuddin; Saputra, Rudi Mardian (Journal of Welding Technology, 2024)
Welding copper and aluminium is a major challenge due to the differences in physical and metallurgical properties of the two materials. Copper has a much higher melting point than aluminium, making it difficult to achieve uniform fusion without overheating. In addition, copper's very high thermal conductivity causes rapid heat transfer, making it difficult to maintain optimal temperatures during welding. The purpose of this study was to determine the effect of TIG welding current on the shear test value and hardness of aluminium-copper material. The stages of the research method began with welding variations in welding current and filler rod types. Furthermore, shear and hardness tests were carried out. Based on the results of the hardness test, the hardness value of the welded material was higher than the parent material. The hardness value of the weld metal was higher at a current of 130A compared to currents of 120A and 140A. While the optimal welding current for copper and aluminium joints in shear test testing using BCuP-2 filler rods is 130 A, where the highest shear strength is achieved